PENGUKURAN TINGKAT KINERJA KEUANGAN DAN KINERJA NON KEUANGAN PADA BANK SYARIAH DI LIMA NEGARA ASIA (Studi Kasus pada Bank Syariah dengan Aset Tertinggi) - Setiawan Setiawan; Putri Wulansari; Rani Putri Kusuma Dewi (Faculty of Economic and Business Universitas STIKUBANK, 2020)
This study aims to determine the financial performance and nonfinancial performance in Islamic banks in seven countries ranked GFIR 2017. This research method uses descriptive quantitative. Quantitaf is used to calculate each ratio and then analyzed descriptively describing the calculation scheme. Measurement of financial performance in this study using the method of Economic Value Added (EVA). Measurement of non-financial performance in this study using maqashid syariah index consists of six ratios of ten ratios available. The ratios consist of the ratio of education funding, research cost ratio, training cost ratio, promotion cost ratio, fair return ratio, functional distribution ratio, interest-free product ratio, profit / profit ratio, personal income ratio, and real sector investment ratio. From the research result, it is found that all sharia banks have good financial performance by generating positive EVA value. In non-financial performance, the result of bank rankings with good performance are as follows: Bank Islam Malaysia, Bahrain Islamic Bank, Bank Mandiri Syariah, Kuwait Finance House, Abu Dhabi Islamic Bank, Al-Rajhi Bank. Keyword: Bank Syariah, Economic Value Added (EVA), Maqashid Syariah Index (MSI)